Experimental Studies on Punching Shear and Impact Resistance of Steel Fibre Reinforced Slag Based Geopolymer Concrete - Srinivasan Karunanithi (Advances in Civil Engineering)
The study was focused on slag based geopolymer concrete with the addition of steel fibre. The slag based geopolymer concrete was under shear load and sudden impact load to determine its response. The punching shear represents the load dissipation of the material and the energy absorption capacity of the geopolymer concrete to impact load. The various percentage of steel fibre in the slag based geopolymer concrete was 0.5%, 1.0%, and 1.5%. Overall the dosage 0.5% of steel fibre reinforced slag based geopolymer shows better results with a punching shear of 224 kN and 1.0% of steel fibre incorporated geopolymer concrete had the better energy absorption capacity with 3774.40 N·m for first crack toughness and 4123.88 N·m for ultimate failure toughness.